1968
DOI: 10.1111/j.1432-1033.1968.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Glycolytic Enzymes to Structure Proteins of the Muscle

Abstract: 1. of the total activity of aldolase can be extracted from rat or rabbit muscle homogenates with aqueous solutions of relatively low ionic strength. The extraction of aldolase from muscle tissue is only complete in aqueous solutions with an ionic strength greater than 0.2. The fraction of aldolase which is set free a t high ionic strength is not located within a special cellular compartment but is present in a bound form and is desorbed in dependence of the ionic strength of the extraction medium.2. F-actin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
1

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(123 citation statements)
references
References 29 publications
(1 reference statement)
4
118
1
Order By: Relevance
“…Many reports of the interactions of the enzyme with F-actin in vitro have been published since Arnold and Pette (1968) first suggested it. The dissociation constants (K d ) of the LDH-F-actin complex are very low, 8 nM (Poglazov and Livanova 1986) to 2.1 M (Arnold et al 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports of the interactions of the enzyme with F-actin in vitro have been published since Arnold and Pette (1968) first suggested it. The dissociation constants (K d ) of the LDH-F-actin complex are very low, 8 nM (Poglazov and Livanova 1986) to 2.1 M (Arnold et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Previous histochemical studies, for example, have shown that muscle LDH, as well as other glycolytic enzymes, is predominantly localized within the isotropic zones of myofibrils (e.g., Dölken et al 1975, and references cited therein). Many biochemical studies have reported that some glycolytic enzymes, including LDH, interact with cytoskeletal proteins such as actin filaments (F-actin), tropomyosin, and troponin (e.g., Arnold and Pette 1968;Arnold et al 1971;Clarke et al 1985;Poglazov and Livanova 1986;Walsh and Knull 1987;Yasykova et al 1990), microtubules, and tubulin (Karkhoff-Schweizer and Knull 1987;Walsh et al 1989;Marmillot et al 1994). This evidence suggests that some glycolytic enzymes exist in both the fluid phase and the solid phase of the cytoplasm and that changes in the equilibrium between the two phases may play a role in the regulation of glycolytic metabolism within cells (Wilson 1978).…”
mentioning
confidence: 99%
“…The interaction of aldolase with actin has been demonstrated histochemically (8,61), biochemically (5,6,8,69), ultrastructurally (16,52), and with immunofluorescence techniques (27). In fact, aldolase was among the first actinbinding proteins to be identified (10), although this interaction was not considered specific at the time.…”
mentioning
confidence: 99%
“…Myogen preparations were obtained from freshly excised white muscle of adult rabbits, essentially by procedures described previously (Arnold & Pette, 1968;Clarke & Masters, 1973, 1974, except that 0.3 M-sucrose / l 0mM-triethanolamine /3 mm -EDTA (pH 7.2 at 40C) (Czok & Bticher, 1960) was used as the extracting medium. This change of procedure proved effective in eliminating the traces of myosin that were present in earlier myogen preparations made in this laboratory (Clarke & Masters, 1973, 1974.…”
Section: Materials and Methods Preparation Ofmyogenmentioning
confidence: 99%
“…From the biological viewpoint this concept of myogen itself as a multi-enzyme complex has been made largely redundant by the detection of interactions between most of the individual glycolytic enzymes and the fibrous components of muscle (Arnold & Pette, 1968;Amberson & Bauer, 1971; Clarke & Masters, 1975). Indeed, Clarke & Masters (1974) have attributed their earlier ultracentrifugal evidence of complex-formation in myogen (Clarke & Masters, 1973) to the presence of myosin in the preparation.…”
mentioning
confidence: 99%